Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) \(\left(3x-2\right)\left(3x-1\right)=\left(3x+1\right)^2\)
<=> \(9x^2-9x+2=9x^2+6x+1\)
<=> \(15x=1\) <=> \(x=\frac{1}{15}\)
b) \(\left(4x-1\right)\left(x+1\right)=\left(2x-3\right)^2\)
<=> \(4x^2+3x-1=4x^2-12x+9\)
<=> \(15x^2=10\) <=> \(x=\frac{2}{3}\)
c) \(\left(5x+1\right)^2=\left(7x-3\right)\left(7x+2\right)\) <=> \(25x^2+10x+1=49x^2-7x-6\)
<=> \(24x^2-17x-7=0\) <=> \(24x^2-24x+7x-7=0\)
<=> \(\left(24x+7\right)\left(x-1\right)=0\) <=> \(\orbr{\begin{cases}x=-\frac{7}{24}\\x=1\end{cases}}\)
d) (4 - 3x)(4 + 3x) = (9x - 3)(1 - x)
<=> 16 - 9x2 = 12x - 9x2 - 3
<=> 12x = 19
<=> x = 19/12
e) x(x + 1)(x + 2)(x + 3) = 24
<=> (x2 + 3x)(x2 + 3x + 2) = 24
<=> (x2 + 3x)2 + 2(x2 + 3x) - 24 = 0
<=> (x2 + 3x)2 + 6(x2 + 3x) - 4(x2 + 3x) - 24 = 0
<=> (x2 + 3x + 6)(x2 + 3x - 4) = 0
<=> \(\orbr{\begin{cases}x^2+3x+6=0\\x^2+3x-4=0\end{cases}}\)
<=> \(\orbr{\begin{cases}\left(x+\frac{3}{2}\right)^2+\frac{15}{4}=0\left(vn\right)\\\left(x+4\right)\left(x-1\right)=0\end{cases}}\)
<=> \(\orbr{\begin{cases}x=-4\\x=1\end{cases}}\)
g) (7x - 2)2 = (7x - 3)(7x + 2)
<=> 49x2 - 28x + 4 = 49x2 - 7x - 6
<=> 21x = 10 <=> x = 10/21
câu c
\(C=\left(2x-1\right)^3+\left(2x-1\right)\left(4x^2+2x+1\right)\)
\(C=\left(2x-1\right)\left[\left(2x-1\right)^2+\left(4x^2+2x+1\right)\right]\)
\(C=\left(2x-1\right)\left[\left(4x^2-4x+1\right)+\left(4x^2+2x+1\right)\right]\)
\(C=2\left(2x-1\right)\left[4x^2-x+1\right]\)
\(2x^3+7x^2+7x+2=0\)
\(\Leftrightarrow\left(2x^3+7x^2+7x\right)+2=0\)
\(\Leftrightarrow x\left(2x^2+7x+7+2\right)=0\)
\(\Leftrightarrow x\left(2x^2+7x+9\right)=0\)
\(\Leftrightarrow x\left(2x^2+6x+3x+9\right)=0\)
\(\Leftrightarrow x\left[\left(2x^2+6x\right)+\left(3x+9\right)\right]=0\)
\(\Leftrightarrow x\left[2x\left(x+3\right)+3\left(x+3\right)\right]=0\)
\(\Leftrightarrow x\left(x+3\right)\left(2x+3\right)=0\)
\(\Leftrightarrow\left\{{}\begin{matrix}x=0\\x+3=0\\2x+3=0\end{matrix}\right.\Leftrightarrow\left\{{}\begin{matrix}x=0\\x=-3\\x=-\dfrac{3}{2}\end{matrix}\right.\)
chúc bạn học tốt!
a) (7x - 8)(7x + 8) - 10(2x + 3)2 + 5x(3x - 2)2 - 4x(x - 5)2
= 49x2 - 64 - 10(4x2 + 12x + 9) + 5x(9x2 - 12x + 4) - 4x(x2 - 10x + 25)
= 49x2 - 64 - 40x2 - 120x - 90 + 45x3 - 60x2 + 20x - 4x3 + 40x - 100x
= 41x3 - 51x2 - 160x - 154
b) (x2 - 3)(x2 + 3) - 5x2(x + 1)2 - (x2 - 3x)(x2 - 2x) + 4x(x + 2)2
= x4 - 9 - 5x2(x2 + 2x + 1) - x4 + 5x3 - 6x2 + 4x(x2 + 4x + 4)
= 5x3 - 6x2 - 5x4 - 10x3 - 5x2 + 4x3 + 16x2 + 16x - 9
= -5x4 - x3 + 5x2 + 16x - 9
Trả lời:
a , ( 7x - 8 ) ( 7x + 8 ) - 10 ( 2x + 3 )2 + 5x ( 3x - 2 )2 - 4x ( x - 5 )2
= 49x2 - 64 - 10 ( 4x2 + 12x + 9 ) + 5x ( 9x2 - 12x + 4 ) - 4x ( x2 - 10x + 25 )
= 49x2 - 64 - 40x2 + 120x - 90 + 45x3 - 60x2 + 20x - 4x3 + 40x2 - 100x
= 41x3 - 11x2 + 40x - 154
b , ( x2 - 3 ) ( x2 + 3 ) - 5x2 ( x + 1 )2 - ( x2 - 3x ) ( x2 - 2x ) + 4x ( x + 2 )2
= x4 - 9 - 5x2 ( x2 + 2x + 1 ) - ( x4 - 2x3 - 3x3 + 6x2 ) + 4x ( x2 + 4x + 4 )
= x4 - 9 - 5x4 - 10x3 - 5x2 - x4 + 2x3 + 3x3 - 6x2 + 4x3 + 16x2 + 16x
= - 5x4 - x3 + 5x2 + 16x - 9
\(\left(x-2\right)\left(x+2\right)\left(x^2-10\right)=72\)
\(\Rightarrow\left(x^2-4\right)\left(x^2-10\right)=72\)
làm nốt(phương trình ước số)
<=>7x(x-1)=(x-1)2
<=>7x(x-1)-(x-1)2 =0
<=>(x-1)(7x-x+1)=0
<=>(x-1)(6x+1)=0
<=>x-1=0 hoặc 6x+1=0
<=>x=1 hoặc 6x=-1
<=>x=1 hoặc x= -1/6
\(7x^2-7x=x^2-2x+1\)
\(\Leftrightarrow7x\left(x-1\right)-\left(x^2-2x+1\right)=0\)
\(\Leftrightarrow7x\left(x-1\right)-\left(x-1\right)^2=0\)
\(\Leftrightarrow\left(x-1\right)\left(7x-x+1\right)\)\(=0\)
\(\Leftrightarrow\left(x-1\right)\left(6x+1\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}x-1=0\\6x+1=0\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=1\\x=-\frac{1}{6}\end{cases}}\)
Vậy.........